The Hepatoprotective Effects of Phak Khom in Hepatitis Treatment - Sychareun Vanphanom; Phimmasone Chanthavongsa; Sackdavong Phoudthavong (Journal of Advances in Medicine and Pharmaceutical Sciences, 2023)
This study investigated the hepatoprotective effects of Phak Khom (Andrographis paniculata) using in vitro and in vivo models. Phak Khom extract showed dose-dependent cytotoxicity on hepatocyte cells, significantly reducing cell viability at concentrations above 100 µg/mL. In addition, the extract showed a reduction in oxidative stress markers, with a 40% reduction in reactive oxygen species (ROS) and inhibition of pro-inflammatory cytokines (TNF-α and IL-6). In vivo, Phak Khom treatment in rats resulted in a significant reduction in liver enzyme levels (ALT and AST), indicating improved liver function. Histopathological analysis revealed decreased liver necrosis and fibrosis, while oxidative stress markers such as malondialdehyde (MDA) were decreased, and superoxide dismutase (SOD) activity was increased. Statistical analysis confirmed the efficacy of the extract at both low and high doses. These findings validate the traditional use of Phak Khom in liver-related disorders and support its potential as an adjunct therapy for hepatitis. However, further clinical studies, especially randomized controlled trials, are essential to confirm its safety and efficacy in humans, and to explore its synergy with conventional treatments.